(untitled) (Global Journal of Human-Social Science, 2012)
Aim : The rainy season UHI characteristics at several sites in Enugu urban were evaluated using paired measurement programme. The aim was to determine the characteristic of urban heat island in the city during rainy season periods. Study Design: Survey Study. Place and Duration of Study: Enugu urban between months of June – July of 2006 and 2007. Methodology. Results : The results indicate that UHI at day and night during rainy season were very different. A downtown –centered heat island was observed both day and night. The day time variations were strongly correlated to the amount of tree shading while in the night, city climate was highly correlated to sky-view factors and thermal properties in the city. Maximum UHI was about 3.20c during the day and hour-to-hour difference was observed at night around (1800hrs to 2300hrs).Conclusion: UHI over Enugu have been analyzed and results reveal some spatial and temporal characteristics. The UHI has been found to occur throughout the day and night during rainy season. Its structure was observed to be greatly influenced by weather, city, metabolism, anthropogenic activities and local geographic features, land-use, land-cover as well as vegetation and population.